2009
DOI: 10.1007/s11605-009-0970-z
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Selective Decontamination of the Digestive Tract (SDD) in Elective Colorectal Surgery

Abstract: Perioperative SDD in elective colorectal surgery seems to reduce postoperative surgical complications including infectious complications and anastomotic leakage. Prospective, randomized, placebo-controlled studies are needed to confirm this conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…This high prophylactic efficacy might be due to specific pharmacokinet profile of these antimicrobials which ensures the bactericidal actions against aerobic and anaerobic pathogenic organisms. Similar results for prophylactic efficacy of ceftriaxone sodium in combination with metronidazole also discussed by Athar et al, (1996), Gravante andCaruso(2009), Lalla (2009), Rau et al, (2000) and Ross et al, (2009).…”
Section: Discussionsupporting
confidence: 82%
“…This high prophylactic efficacy might be due to specific pharmacokinet profile of these antimicrobials which ensures the bactericidal actions against aerobic and anaerobic pathogenic organisms. Similar results for prophylactic efficacy of ceftriaxone sodium in combination with metronidazole also discussed by Athar et al, (1996), Gravante andCaruso(2009), Lalla (2009), Rau et al, (2000) and Ross et al, (2009).…”
Section: Discussionsupporting
confidence: 82%
“…Alternatively, it has been demonstrated that SDD with antibiotics prior to resection of colorectal carcinoma reduced post-surgical infectious complications and anastomotic leakage. 54 We observed that treatment of rats with a SDD regime prior to colectomy resulted in diminished adherence of tumor cells in the liver, compared to untreated animals. Taken together, it is likely that the bacterial load as well as blood endotoxin concentrations are reduced after SDD, which may lead to a decreased risk of developing liver metastases and improved oncological outcome for patients.…”
Section: Discussionmentioning
confidence: 82%
“…The results are promising and suggest that postoperative infectious complications can be reduced by applying SDD before and after surgery [5]. In a prospective randomized controlled trial by our group, perioperative SDD did indeed decrease infectious complications, and also the rate of anastomotic leakage (accepted for publication).…”
Section: Introductionmentioning
confidence: 85%
“…Only one study on the use of perioperative SDD with a combination of polymyxin B sulfate, tobramycin and amphotericin B in elective colorectal surgery has been published in full. This retrospective study showed that the use of perioperative SDD in elective colorectal surgery in addition to standard parenteral prophylaxis significantly decreased infectious complications [5]. …”
Section: Discussionmentioning
confidence: 99%